Whole Earth Telescope observations of the helium interacting binary PG 1346+082 (CR bootis) - Provencal, Judith L. (2015)
We present our analysis of 240 hr of white-light, high-speed photometry of the dwarf nova-like helium variable PG 1346+082 (CR Boo). We identify two frequencies in the low-state power spectrum, at 679.670±0.004 μHz and 669.887±0.008 μHz. The 679.670 μHz variation is coherent over at least a 2 week time span, the first demonstration of a phase-coherent photometric variation in any dwarf nova-like interacting binary white dwarf system. The high-state power spectrum contains a complex fundamental with a frequency similar, but not identical, to the low-state spectrum, and a series of harmonics not detected in low state. We also uncover an unexpected dependence of the high-frequency powerÏs amplitude and frequency structure on overall system magnitude. We discuss these Ðndings in light of the general AM CVn system model, particularly the implications of the high-order harmonics on future studies of disk structure, mass transfer, and disk viscosity.